Find the general solution of each of the following
i) (2xsiny+y3ex)dx +(x2cosy+3y2ex)dy=0
ii) (ysec2x+secxtanx)dx + (tanx+2y)dy=0
iii)(yex+2ex+y2)dx+(ex+2xy)dy=0 y(0)=6
iv)(2xcosy+3x2y)dx+(x3-x2siny-y)dy=0 y(1)=3
i)
"(2x\\sin y+y^3e^x)dx +(x^2\\cos y+3y^2e^x)dy=0""P=2x\\sin y+y^3e^x, \\dfrac{\\partial P}{\\partial y}=2x\\cos y+3y^2e^x"
"Q=x^2\\cos y+3y^2e^x, \\dfrac{\\partial Q}{\\partial x}=2x\\cos y+3y^2e^x"
"\\dfrac{\\partial P}{\\partial y}=\\dfrac{\\partial Q}{\\partial x}"
"\\dfrac{\\partial u}{\\partial x}=P"
"\\dfrac{\\partial u}{\\partial y}=Q"
"u(x,y)=\\int P dx+\\varphi(y)"
"=\\int (2x\\sin y+y^3e^x)dx+\\varphi(y)"
"=x^2\\sin y+y^3e^x+\\varphi(y)"
"\\dfrac{\\partial u}{\\partial y}=x^2\\cos y+3y^2e^x+\\varphi'(y)"
"=x^2\\cos y+3y^2e^x=Q"
Then "\\varphi'(y)=0"
The general solution of the equation is defined by the following implicit expression:
"x^2\\sin y+y^3e^x=C,"
where "C" is an arbitrary real number.
ii)
"(y\\sec^2x+\\sec x\\tan x)dx + (\\tan x+2y)dy=0""P=y\\sec^2x+\\sec x\\tan x, \\dfrac{\\partial P}{\\partial y}=\\sec^2x"
"Q=\\tan x+2y, \\dfrac{\\partial Q}{\\partial x}=\\sec^2x"
"\\dfrac{\\partial P}{\\partial y}=\\dfrac{\\partial Q}{\\partial x}"
"\\dfrac{\\partial u}{\\partial x}=P"
"\\dfrac{\\partial u}{\\partial y}=Q"
"u(x,y)=\\int P dx+\\varphi(y)"
"=\\int (y\\sec^2x+\\sec x\\tan x)dx+\\varphi(y)"
"=y\\tan x+\\sec x+\\varphi(y)"
"\\dfrac{\\partial u}{\\partial y}=\\tan x+\\varphi'(y)"
"=\\tan x+2y=Q"
Then "\\varphi'(y)=2y"
The general solution of the equation is defined by the following implicit expression:
where "C" is an arbitrary real number.
iii)
"(ye^x+2e^x+y^2)dx+(e^x+2xy)dy=0""P=ye^x+2e^x+y^2, \\dfrac{\\partial P}{\\partial y}=e^x+2y"
"Q=e^x+2xy, \\dfrac{\\partial Q}{\\partial x}=e^x+2y"
"\\dfrac{\\partial P}{\\partial y}=\\dfrac{\\partial Q}{\\partial x}"
"\\dfrac{\\partial u}{\\partial x}=P"
"\\dfrac{\\partial u}{\\partial y}=Q"
"u(x,y)=\\int P dx+\\varphi(y)"
"=\\int (ye^x+2e^x+y^2)dx+\\varphi(y)"
"=ye^x+2e^x+xy^2+\\varphi(y)"
"\\dfrac{\\partial u}{\\partial y}=e^x+2xy+\\varphi'(y)"
"=e^x+2xy=Q"
Then "\\varphi'(y)=0"
The general solution of the equation is defined by the following implicit expression:
where "C" is an arbitrary real number.
"y(0)=6"
"C=8"
The solution of the given equation is
iv)
"(2x\\cos y+3x^2y)dx+(x^3-x^2\\sin y-y)dy=0""P=2x\\cos y+3x^2y, \\dfrac{\\partial P}{\\partial y}=-2x\\sin y+3x^2"
"Q=x^3-x^2\\sin y-y, \\dfrac{\\partial Q}{\\partial x}=3x^2-2x\\sin y"
"\\dfrac{\\partial P}{\\partial y}=\\dfrac{\\partial Q}{\\partial x}"
"\\dfrac{\\partial u}{\\partial x}=P"
"\\dfrac{\\partial u}{\\partial y}=Q"
"u(x,y)=\\int P dx+\\varphi(y)"
"=\\int (2x\\cos y+3x^2y)dx+\\varphi(y)"
"=x^2\\cos y+x^3y+\\varphi(y)"
"\\dfrac{\\partial u}{\\partial y}=-x^2\\sin y+x^3+\\varphi'(y)"
"=x^3-x^2\\sin y-y=Q"
Then "\\varphi'(y)=-y"
The general solution of the equation is defined by the following implicit expression:
where "C" is an arbitrary real number.
"y(1)=3"
"C=2\\cos3+4.5"
The solution of the given equation is
Comments
Leave a comment